The associations between skin advanced glycation end-products and Framingham cardiovascular risk in different age groups - Wang, Yina; Liang, Shangyan; Zhou, Ying; Tang, Xiumei; Ye, Na; Huang, Weilan; Tang, Xixiang; Jiang, Boxiong; Pan, Yunfeng (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveAdvanced glycation end-products (AGEs) may contribute to the pathogenesis of atherosclerotic cardiovascular disease (ASCVD), potentially influencing its development and progression differently at various life stages. This study aimed to elucidate the associations between AGEs and the risk of ASCVD across different age groups.MethodsIn this cross-sectional study, 1,240 subjects were enrolled and divided into three groups (Group Ⅰ, 20–39 years old, n = 468; Group Ⅱ, 40–59 years old, n = 471; Group Ⅲ, 60–79 years old, n = 301). Skin AGEs were measured by skin autofluorescence (SAF). ASCVD risk was assessed by a validated Framingham risk score calculator. Other proven ASCVD risk factors were also measured, including glycosylated hemoglobin, uric acid, lipid profile, homocysteine, and cystatin C.ResultsAn increasing trend in skin AGEs was observed from Group Ⅰ to Group Ⅲ. Skin AGEs were significantly associated with ASCVD risk in all subjects (OR 1.029, 95% CI 1.003–1.056, P = 0.018), independent of some of the proven cardiovascular risk factors. This association was particularly significant in individuals aged 40–59 and 60–79 (OR = 1.047, 95% CI: 1.025–1.069; OR = 1.022, 95% CI: 1.002–1.042; both P < 0.05). ROC analysis showed that skin AGEs predicted the diagnosis of medium or high ASCVD risk in the pooled group, Group Ⅱ, and Group Ⅲ.ConclusionOur study substantiates that skin AGEs play an important role as an independent risk factor for ASCVD, highlighting their significance beyond traditional risk assessment models, particularly in middle-aged and older populations.